ELF writing assessment: Lecturers' perceptions and practices - Nguyễn Thị Tuyết Nhung (Trường Đại Cần Thơ, 2022)
With respect to the important role of writing assessment forESL/ EFL students,numerous educators and teachers have investigated various dimensions of writingassessment, especially designing writing assessment tasks and scoring writing papers.As an effort to contribute to enriching empirical evidence in the field, this researchaimed at exploring perceptions and practices of lecturers towards writing assessmentof first-and second-year English major students. This paper also aimed to find out acorrelation of lecturers’ perceptions with their practices of writing assessment. Bothquantitative and qualitative methods including questionnaires and interviews forcollecting the data were used in the study. Twenty-eight lecturers (9 males and 19females) teaching academic writing for English major students infouruniversitieslocated in the Mekong Delta participated in this study. Major findings of the studyindicated that the participants had a positive perception towards the basic issues indesigning writing assessment tasks and analytic scoring method. In addition, the studyfound out the correlation between lecturers’ perceptions and practices of the basicissues in designing task and analytic scoring method, but there was no correlationbetween their perceptions and practices of holistic scoring method. The interview datasupported the questionnaire’s findings. Based on the study’s findings, discussions andpedagogical implications and recommendations were also made.